Implementing a social-ecological model of health in Wales - Rothwell, H; Shepherd, M; Murphy, S; Burgess, S; Townsend, N; Pimm, C (2010)
Purpose: The purpose of this paper is to assess the implementation of the Welsh Network of Healthy School Schemes (WNHSS) at national, local and school levels, using a systems approach drawing on the Ottawa Charter. Design/methodology/approach: The approach takes the form of a single-case study using data from a documentary analysis, interviews with Healthy Schools Co-ordinators (n=23) and stakeholder (n~93) discussion of interim findings at three regional workshops. Findings: There was almost universal adherence to a national framework based on Ottawa Charter principles. Substantial progress had been made with advocacy and mediation, although the framework provided less specific guidance regarding enablement. All-Wales training for co-ordinators, the commitment of co-ordinators to working across administrative and professional boundaries, and support from local education and health partnerships, were important determinants of healthy school schemes' growth and efficiency. Primary schools were more successful than secondary schools in embedding health-related changes. Research limitations/implications: Although findings are largely based on indirect evidence, the use of a social-ecological model of evaluation provided valuable insights into implementation processes at multiple levels. Findings suggest that strong national support benefits programme development and dissemination and should include effective monitoring of local performance. The national strategic environment was influential at all levels of programme implementation. Priorities for further research include application of the social-ecological model and organisational theory to investigate indicators of sustainability and influences on inequalities in health in school health promotion programmes. Originality/value: The review illustrates the importance of evaluating health promotion programmes at multiple levels using a systems approach. © Emerald Group Publishing Limited.